THE RELATIONSHIP OF SELF-EFFICACY WITH PERCEIVED FUTURE EMPLOYABILITY IN JOB SEEKERS OF HIGHER COLLEGE GRADUATES IN PADANG CITY - Tuffa Humaira Putri; Rahayu Hardianti Utami (In Trend : International Journal of Trends in Global Psychological Science and Education, 2023)
Over the last few years, unemployment in Indonesia has been dominated by the educated workforce. Unemployed people with the highest education completed at a university reached 673,485 people (Central Statistics Agency, 2022). College graduates who have job seeker status experience difficulty in obtaining employment. Therefore, college graduates need to be ready to enter the world of work. Perceived future employability refers to the perception of how employable he will be in the future and ready to enter the job market. The perception of self-readiness is preceded by a person's belief in his or her abilities. The aim of this research is to determine the relationship between self-efficacy and perceived future employability among job seekers who graduate from universities in Padang City. This research uses the theory of perceived future employability and self-efficacy. The sampling technique used in this research was purposive sampling. This research uses product moment correlation test data analysis techniques. It was found that the value of r = 0.631 with a value of p = 0.000 (p < 0.05) means that Ha was accepted, so it is known that there is a significant positive relationship between self-efficacy and perceived future employability in job seekers who graduated from universities in the city of Padang.